Implementation of Balanced Scorecard as a Benchmarking Tool in Public Organizations - Wijaya, Uki Budi Wijaya; Suprayogi, Suprayogi; Zahra, Indri Eliza; Suripto, Suripto; Holiawati, Holiawati (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
In the era of globalization and rapid information technology development, public organizations in Indonesia face demands to improve performance and accountability. The Balanced Scorecard (BSC) is a strategic management tool that can help public organizations focus more on long-term vision and strategy while enhancing accountability and transparency in resource management. This study aims to explore the implementation of BSC as a benchmarking tool in several public organizations in Indonesia. Through case studies, this research identifies challenges faced and best practices in BSC implementation. The results show significant improvements in financial performance in 2022 compared to 2021, despite challenges such as limited resources and resistance to change. Recommendations to enhance BSC implementation effectiveness include training, leadership commitment, and adjustments to the local context. This study is expected to make a significant contribution to the development of performance management in Indonesia's public sector.